Valores hematológicos de morcegos hematófagos Desmodus rotundus (E. Geoffroy, 1810) mantidos em cativeiro - Almeida, Breno F. M. de [UNESP] (2010)
Hematological values from captive vampire bats Desmodus rotundus (E. Geoffroy, 1810). Desmodus rotundus is one of the hematophagous bat species that are responsible for significant losses to livestock and has important involvement on public health. The great interest on this bat species made it becomes the target of many investigations a required its maintenance in laboratories. Similarly to others mammals, hematological evaluation has been utilized to assess the health and morbidity state of bats, however there are scarce studies with captive bats. The aim of this study was to investigate the hypothesis that is possible to feed the vampire bat D. rotundus with frozen blood treated with citrate during a long captivity period without hematological dyscrasias. Therefore, complete blood count was performed monthly from 15 adult females kept for 345 days in cages and fed with frozen blood added to citrate. The erythrocyte concentration (9.02 ± 1.43 x1012/L), PCV (0.47 ± 0.08 L/L) and hemoglobin (163.9 ± 31.5 g/L) obtained from free-living bats (immediately after capture) were lower or similar to those obtained after 345 days of captivity, presenting erythrocytes’ count of 11.01 ± 0.82 x1012/L, packed cell volume of 0.50 ± 0.05 L/L and hemoglobin level of 158 ± 10.1 g/L. The total white blood cell (11.09 ± 6.07 x109 /L) and segmented neutrophil counts (9.85 ± 3.5 x109 /L) of free living D. rotundus decreased significantly after 345 days of captivity, with values of 3.98 ± 1.98 and 1.87 ± 978.6 x109 /L respectively, which are similar to bats from temperate regions in hibernation period. This study proved that is possible to feed D. rotundus for long periods of captivity with citrated blood without the occurrence of anemia, erythrocyte or other hematologic dyscrasia